The Effect of Reciprocal Teaching Learning Model and Self-Concept on Reading Comprehension Ability - Tantowie, Tanto Aljauharie; Sunendar, Dadang; Rahman; Hartati, Tatat (Jurnal Pendidikan Indonesia, 2022)
The reading ability of students in the field is still very worrying. This is reinforced by the low ability of students to understand material or questions that require higher-order thinking skills. The low reading comprehension ability can be seen from the low literacy ability of students based on PISA rankings. This study aims to analyze the effectiveness of the reciprocal teaching model on students' reading comprehension skills in terms of students' self-concept levels. The approach used in this research is quantitative with a quasi-experimental method. The participants of this study were 100 elementary school students who were divided into two groups of 50 students each in the experimental and control groups. Data was collected through reading comprehension tests and observations. Data analysis was performed by two-way ANOVA. The results showed that the Reciprocal Teaching model gave a more significant contribution to students' reading comprehension skills compared to conventional methods, especially for students who had low self-concept. Based on the findings above, it is concluded that the Reciprocal Teaching learning model has an effect on students' reading comprehension skills. Both reciprocal and conventional learning models have the same effect on students who have high self-concept. The implication of this research is that teachers must choose a learning model that can accommodate all students, not only students with high academic abilities, but also students with low academic abilities.